STUDENTS’ BELIEFS ON THE ENGLISH LEARNING IMPORTANCES FOR AGRIBUSINESS MAJOR STUDENTS AT ISLAMIC UNIVERSITY OF INDRAGIRI - Sri Erma Purwanti; Maizarah (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research aimed to know students’ beliefs toward the importance of English Learning for Agribusiness students at Islamic University of Indragiri. The research design was qualitative approach. There were 15 students of Agribusiness major took part as participants in this study. To collect the data, 17 open-ended questionnaire was distriuted to them using 5 themes: language learning aptitude, difficulty of learning language, nature of language learning, learning and communication strategies, and motivation and expectations. The answers of the questionnaire were analyzed in four steps, namely data collection, data reduction, data display, and verification. The result of this study shows that the students of agribusiness major believe that learning English is very important for them.